Theoretical study of singlet and triplet excitation energies in oligothiophenes - Fabiano, E.; Della Sala, Fabio; Cingolani, R.; Weimer, Martin; Görling, Andreas (Journal of Physical Chemistry A, 2005)
We have analyzed singlet and triplet excitation energies in oligothiophenes (up to five rings) using time-dependent density-functional theory (TD-DFT) with different exchange-correlation functionals and compared them with results from the approximate coupled-cluster singles and doubles model (CC2) and experimental data. The excitation energies have been calculated in geometries obtained by TD-DFT optimization of the lowest excited singlet state and in the ground-state geometries of the neutral and anionic systems. TD-DFT methods underestimate photoluminescence energies but the energy difference between singlet and triplet states shows trends with the chain-length similar to CC2. We find that the second triplet excited state is below the first singlet excited state for long oligomers in contrast with the previous assignment of Rentsch et al. (Phys. Chem. Chem. Phys. 1999, 7, 1707). Their photodetachment photoelectron spectroscopy measurements are better described by considering higher triplet excited states. © 2005 American Chemical Society.